Examining the Relationships among Consumers' Health Perception, Satisfaction, and Behavioral Intentions in Vegetable Restaurants - Yang, Ai-Shih (Archives of Business Research, 2023)
The study examined the relationships among consumers' health perception, customer satisfaction, and behavioral intentions in vegetable restaurants. Questionnaire investigation was performed and 281 copies were received. The data was analyzed through multiple regression analysis. The result revealed that: (1) "Dietary Control" and "Novel Flavors" in customers’ health perception have significant impacts on satisfaction, and (2) customer satisfaction positively influence on behavioral intentions. "Dietary Control," especially when considering its impact on various aspects of customer satisfaction, underscores the significance of health-related factors in shaping customer experiences and perceptions. We recommend future research exploring the correlation between health perception and food and agricultural education, all while promoting healthier and more sustainable lifestyles.